Teaching peer reviewing to medical students through authentic peer reviews: How to build the next generation of scholars - Schmidt, Cindy; Thiel, Grace; Murtha, Celeste (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2023)
Implication StatementThe peer review process is a critical step in producing sound scientific literature, traditionally conducted by professionals well-established in their field. It is uncommon for students, even at the graduate level, to contribute. Faculty created a novel course in which 18 medical students (nine per year) delivered peer reviews to the Canadian Medical Education Journal (CMEJ). The positive feedback and competency gained is described in the students’ Letter to the Editor. While this course was initially created to benefit students, it has also helped to address a known deficit in peer reviewers.